A atuação do vereador na câmara municipal de Araraquara: processo legislativo em dois momentos - Ruggiero Junior, Nelson (Universidade Federal de São Carlos, 2005)
This case study had the aim of analyzing the interaction between the Executive and the Legislative powers in the municipal district of Araraquara in two periods; 1997 to 1999 during the government of Waldemar de Santi, from PPB party , and 2001 to 2003 government of Edson Antonio da Silva, from PT party. Based on the neoinstitutional theoretical approach and supported by legislative studies of the three political spheres, the present study focused on observing the councilmen behavior adopted in the recent decisional process of Araraquara, evaluating the political-institutional relationship, as well as the partisan variable. To this end, quantitative and qualitative analyses are taken together. The submissive behavior of Legislative in the legal production showed a pathway that reproduces evidences found in other studies in several levels of government. However, in the second moment studied it was noticed that a space was given to improve the instances of the City Hall Commission Studies case , at the same time that the agenda power and the relevance of the Executive proposals increased
Keywords: Poder legislativo; Vereador; Sistemas políticos; Câmara municipal; Instituição política; Decisional Process; City Hall, Political Institutions; Legislative; Councilmen; Political Behavior; Municipal District; Mayor; CIENCIAS HUMANAS::CIENCIA POLITICA